Podmiot groteskowy w dramatach Olega Bogajewa - Juchniewicz, Agnieszka (Studia Rossica Posnaniensia, 2020)
The article analyses three dramas written by Oleg Bogayev (The Russian National Postal Service. A Room of Laughter for a Lonely Pensioner; Bashmachkin and Sansara). The purpose of the work was primarily to expose various forms, due to which we can talk about the grotesqueness of the subject, i.e. the relationship I – Others, the violation of the boundary between the categories of significant and signified, subject-object relations, the subject of the act of behaviour and the act of speech as well as the occurrence of the Voice as a separate unit from the subject. The author emphasises the fact that the contemporary figure of the subject has been reduced to the language level and experiences a crisis of self-identification, which in turn leads to the crisis of the drama itself. Comic characters balance between the real and the fantastic world. Their statements are often pictures-simulations, heavily saturated with irony, the grotesque and absurdity.